AUXI - Montellano, Madalena (2021)
AUXI is an interaction design project focused on Affective Computing, more specifically on emotional design. Nowadays, society is regularly exposed to stress and anxiety, therefore, our project focuses on panic attacks, a condition that affects a large part of the world population. AUXI aims to help users coping with and avoiding this condition related to mental health, so that they are not limited by these attacks and are able to achieve a better quality of life.